Law basis for the development of competitive production as the main branch of agrarian policy in Ukraine - Самсонова, Я. О. (Theory and practice of jurisprudence, 2016)
Problem setting: In modern conditions, the integration of the agricultural production and the industry in Ukraine are taking new forms, and therefore require a detailed analysis of the main trends of development, particularly in the sphere of the law regulation of these relations. Recent of research and publications analysis. Among the scientists who have been studying some of the legal status of subjects of agricultural production, the process of integration and cooperation in agriculture, it should be noted L.О. Pankova, A.M. Stativka, V.Y. Urkevich, G.E. Bystrov, M.F. Kropivko, M.I. Malik. The object of the article. The aim of this article is to study the organizational and law issues of integration and cooperation as the ways of improving the efficiency of subject`s work of agrarian sector and the priority of agrarian policy of Ukraine. The main body of the article. The main problems of the development of competitive agricultural production on the basis of integration and cooperation are defined; the main branches of the integration processes in agriculture are discussed; the organizational and law issues of creation and functioning of effective forms of management in the agricultural sector, in particular the agricultural holding companies, industrial and financial groups, associations, agricultural clusters are studied; the benefits of cooperative farming in agriculture are defined; the priorities of state regulatory policy of Ukraine are stated. Conclusions of the research. The Integration and cooperation, as the branch of agricultural policy must solve one of the main objectives of the organization and functioning of the agricultural market – the formation of a favorable economic environment by providing a rational construction of the exchange between the spheres of agriculture and the solution of the problem of disparity of prices. However, the prospects of any branch of integration in the development of the agricultural sector depends on the balance of interests of all the security and interoperability and complementarity of the production sphere, agriculture sphere with the service, the logistics spheres and the social development of the village.